2022
DOI: 10.3390/ijms23169370
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Metabolome and Transcriptome Analysis Reveals the Regulatory Network of Flavonoid Biosynthesis in Response to MeJA in Camelliavietnamensis Huang

Abstract: Flavonoids are secondary metabolites widely found in plants, which perform various biological activities, such as antiinflammation, antioxidation, antitumor, and so on. Camellia vietnamensis Huang, a species of oil-tea Camellia tree, is an important woody oil crop species widely planted on Hainan Island, which provides health benefits with its high antioxidant activity and abundant flavonoid content. However, very little is known about the overall molecular mechanism of flavonoid biosynthesis in C. vietnamensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The genes associated with flavonoid biosynthesis are mainly classified into structural and regulatory genes [41]for instance, CHS, FLS, F3H, F3 H, C4H, etc. C4H plays an important role in flavonoid biosynthesis [42][43][44]. Correlation analysis showed that C4H at all three ripening stages positively regulated flavonoids including luteolin, hesperetin, homoeriodictyol, phloretin, butin, aromadendrin, naringenin chalcone, and pinobanksin.…”
Section: Discussionmentioning
confidence: 99%
“…The genes associated with flavonoid biosynthesis are mainly classified into structural and regulatory genes [41]for instance, CHS, FLS, F3H, F3 H, C4H, etc. C4H plays an important role in flavonoid biosynthesis [42][43][44]. Correlation analysis showed that C4H at all three ripening stages positively regulated flavonoids including luteolin, hesperetin, homoeriodictyol, phloretin, butin, aromadendrin, naringenin chalcone, and pinobanksin.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-six pairs of SSR primers were selected for pre-screening based on the transcriptome data of C. vietnamensis (NCBI accession number: PRJNA825399) [ 24 ], in which 15 fluorescently labeled SSR primers were selected for further research ( Table 2 ). In addition, nine pairs of primers with good polymorphism were screened, referring to Song’s study ( Table 2 ) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, most studies have only explored the molecular mechanisms by which natural product from traditional Chinese medicine induces ferroptosis through a single pathway. Nevertheless, traditional Chinese medicine formulas and patent medicines widely used in clinical practice possess the characteristics of “multiple components, multiple targets, and multiple effects” ( Yan et al, 2022 ). In future research, we should explore the molecular mechanisms of traditional Chinese medicine in regulating ferroptosis from multiple pathways and perspectives, construct “components-targets/pathways-disease” pharmacological network, and conduct relevant clinical trials.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%